A Comparative Proteomic Analysis of Praziquantel-Susceptible and Praziquantel-Resistant Schistosoma mansoni Reveals Distinct Response Between Male and Female Animals - Pinto-Almeida, António; Mendes, Tiago M. F.; Ferreira, Pedro; Abecasis, Ana B.; Belo, Silvana; Anibal, Fernanda F.; Allegretti, Silmara M.; Galinaro, Carlos A.; Carrilho, Emanuel; Afonso, Ana (Frontiers in Tropical Diseases, 2021)
Schistosomiasis is a chronic neglected tropical disease saddling millions of people in the world, mainly children living in poor rural areas. Praziquantel (PZQ) is currently the only drug used for the treatment and control of this disease. However, the extensive use of this drug has brought concern about the emergence of PZQ-resistance/tolerance by Schistosoma mansoni. Studies of Schistosoma spp. genome, transcriptome, and proteome are crucial to better understand this situation. In this in vitro study, we compare the proteomes of a S. mansoni variant strain stably resistant to PZQ and isogenic to its fully susceptible parental counterpart, identifying proteins from male and female adult parasites of PZQ-resistant and PZQ-susceptible strains, exposed and not exposed to PZQ. A total of 60 Schistosoma spp. proteins were identified, some of which present or absent in either strain, which may putatively be involved in the PZQ-resistance phenomenon. These proteins were present in adult parasites not exposed to PZQ, but some of them disappeared when these adult parasites were exposed to the drug. Understanding the development of PZQ-resistance in S. mansoni is crucial to prolong the efficacy of the current drug and develop markers for monitoring the potential emergence of drug resistance.